Overcoming the Brain Barriers: From Immune Cells to Nanoparticles. (January 2020) - Charabati, Marc; Rabanel, Jean-Michel; Ramassamy, Charles; Prat, Alexandre
Abstract : Nanoparticulate carriers, often referred to as nanoparticles (NPs), represent an important pharmacological advance for drug protection and tissue-specific drug delivery. Accessing the central nervous system (CNS), however, is a complex process regulated by mainly three brain barriers. While some leukocyte (i.e., immune cell) subsets are equipped with the adequate molecular machinery to infiltrate the CNS in physiological and/or pathological contexts, the successful delivery of NPs into the CNS remains hindered by the tightness of the brain barriers. Here, we present an overview of the three major brain barriers and the mechanisms allowing leukocytes to migrate across each of them. We subsequently review different immune-inspired and -mediated strategies to deliver NPs into the CNS. Finally, we discuss the prospect of exploiting leukocyte trafficking mechanisms for further progress. Highlights: Most drug delivery strategies perform suboptimally in the CNS due to the presence of three major brain barriers: the blood–brain barrier, the blood–leptomeningeal barrier, and the blood–cerebrospinal fluid barrier. Immune cells use a plethora of molecules to bypass the different barriers and infiltrate the CNS under homeostasis and in diverse pathological contexts. Nanoparticulate carriers, often shortened to nanoparticles (NPs), have recently emerged as superior vehicles capable of protecting drugs while also promoting tissue-specific delivery, but remain ineffective in transporting pharmaceutical agents into the CNS. Exploiting the molecular and cellular pathways used by immune cells to overcome the protective brain barriers may prove useful for enhancing NP delivery into the CNS.